Innovation ecosystems: A critical examination. (August 2016) - Oh, Deog-Seong; Phillips, Fred; Park, Sehee; Lee, Eunghyun
Abstract: Publications pushing the "innovation ecosystem" meme have added valuable dimensions to the economic development discussion. The phrase has captured the imagination of policy makers and has motivated public initiatives of substantial magnitude. This paper reviews the concept of innovation ecosystems as it is set forth in the academic and trade literature, and asks, "What is gained from adding 'eco-' to our treatment of national and regional innovation systems?" The answer is, "Very little, and the risks outweigh the benefits." Innovation ecosystem is not yet a clearly defined concept, much less a theory. Moreover, the idea carries pitfalls, notably its over-emphasis on market forces, and its flawed analogy to natural ecosystems. The prospect that the phrase "innovation ecosystem" is here to stay, in investment and economic development circles, implies a research gap, and indicates caution in using the phrase in rigorous research. The paper describes the gap, indicates directions for bridging it, and offers recommendations for prudent use of "ecosystem" terminology. Highlights: Writers on "innovation ecosystems" have added some valuable ideas to the innovation discussion. These ideas do not depend on "eco-" terminology. Appending "eco-" to "innovation systems" adds nothing of substance. "Innovation ecosystem" is a faulty analogy to natural ecosystems, leading to cognitive dissonance and possibly harmful policy choices. Researchers should avoid the ecosystem term, or use it with consideration of the cautions detailed in this paper. These cautions encourage rigor in the development of innovation studies and practice.